KEUNGGULAN DAN MANFAAT SERTIFIKASI LOGO HALAL PRODUK KOSMETIK (Ahkam: Jurnal Hukum Islam, 2023)
The background of the problem with globalization, free trade and the Asian Economic Community (AEC) has led to an increase in the circulation of cosmetic products in Indonesian society. Indonesia is a country with the largest Muslim population in the world. In Article 29 paragraph (2) of the 1945 Constitution of the Republic of Indonesia it is stated that "The state guarantees every resident to embrace their religion according to their beliefs". The problem formulation of this paper is what are the advantages and benefits of a halal logo certificate for cosmetic products traded in the community. The purpose of writing is to find out the advantages and benefits of a halal logo certificate on cosmetic products traded in society. The research method used in writing is library research in the form of secondary data using primary legal materials, secondary materials and tertiary materials. The conclusion of this paper is to Obtain the Advantages and Benefits of Halal Logo Certification for Cosmetic Products. LPPOM MUI forms an auditor team to conduct an audit during the production process and audit results are submitted to the MUI Fatwa Commission to obtain a halal determination and the MUI issues a halal certificate. non-halal products.